2017
DOI: 10.1038/s41467-017-01662-6
|View full text |Cite
|
Sign up to set email alerts
|

Unusual scaling laws for plasmonic nanolasers beyond the diffraction limit

Abstract: Plasmonic nanolasers are a new class of amplifiers that generate coherent light well below the diffraction barrier bringing fundamentally new capabilities to biochemical sensing, super-resolution imaging, and on-chip optical communication. However, a debate about whether metals can enhance the performance of lasers has persisted due to the unavoidable fact that metallic absorption intrinsically scales with field confinement. Here, we report plasmonic nanolasers with extremely low thresholds on the order of 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 46 publications
1
64
1
Order By: Relevance
“…Regardless of the application and due to their ultrasmall size, nanolasers have unique advantages for this type of requirement as low consumption becomes an essential need. Their realization relies historically on semiconductor technologies based on heterostructures [1,2], but was extended recently to spasers [3] whose plasmonic effects allow resonant cavities of a volume much lower than λ 3 , with λ the wavelength of operation in vacuum [4][5][6]. Because of these small ultimate sizes, only a few individual emitters can be involved in a single device, which results in a very small number of photons emitted and an increasing importance of the fluctuations due to the quantum nature of processes, either optical or electrical.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the application and due to their ultrasmall size, nanolasers have unique advantages for this type of requirement as low consumption becomes an essential need. Their realization relies historically on semiconductor technologies based on heterostructures [1,2], but was extended recently to spasers [3] whose plasmonic effects allow resonant cavities of a volume much lower than λ 3 , with λ the wavelength of operation in vacuum [4][5][6]. Because of these small ultimate sizes, only a few individual emitters can be involved in a single device, which results in a very small number of photons emitted and an increasing importance of the fluctuations due to the quantum nature of processes, either optical or electrical.…”
Section: Introductionmentioning
confidence: 99%
“…where   QQ ) limits. Since the typical emission spectrum of a gain material (dyes, QDs) is usually ~10 nm and 12 res~1 0 10 Q  , in nanophotonics we usually deal with the bad resonator case and, therefore, the Purcell factor tot F can be defined as res eff / QV [143]. In turn, in the good resonator limit (disk cavity, defect in a photonic crystal, etc.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A similar structure (CdS square on top of an Au substrate) has been comprehensively studied in Ref. [143] and compared to the same but placed on SiO2 substrate (photonic nanolaser). It has been experimentally demonstrated that the Au nanolasers have unusual scaling laws allowing them to be more compact and faster with lower power consumption when their cavity size approaches or surpasses the diffraction limit, whereas the photonic nanolasers do not demonstrate such a performance.…”
mentioning
confidence: 99%
“…Hua Lu, 1, * Siqing Dai, 1 Zengji Yue, 2 Yicun Fan, 1 Huachao Cheng, 1 Jianglei Di, 1 Dong Mao, 1 Enpu Li, 1 and Jianlin Zhao 1 Surface plasmons (SPs), light-driven oscillation of free electrons along the conductor-dielectric interface, play a crucial role in current development of optical physics and functional devices due to the remarkable capabilities of confining light at the subwavelength scale, enhancing the near-field intensity, and overcoming the diffraction limit of light. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Over the past two decades, numerous unusual optical phenomena were observed in metal-based plasmonic systems, such as extraordinary optical transmission, [15] plasmonic guiding, [3] plasmonic resonance, [16] Optically-triggered memory effect, [6] meta-holography, [7] Raman scattering, [8] optical activity, [9] nonlinear enhancement, [10,17] plasmonic trapping, [11] phase manipulation, [18] plasmon-induced transparency, [19,20] quantum plasmonics, [21] and plasmonic focusing. [22,23] Based on these plasmonic responses, a large number of optical functionalities were proposed and investigated, for example nanolasers, [12,24] holographic imaging,…”
Section: Sb2te3 Topological Insulator: Surface Plasmon Resonance and mentioning
confidence: 99%